The Cyanobacteria-Dominated Sponge Dactylospongia elegans in the South China Sea: Prokaryotic Community and Metagenomic Insights - Gao, Zhao-Ming; Zhou, Guo-Wei; Huang, Hui; Wang, Yong (Frontiers in Microbiology, 2017)
The South China Sea is a special reservoir of sponges of which prokaryotic communities are less studied. Here, a new record of the sponge Dactylospongia elegans is reported near the coast of Jinqing Island in the South China Sea, and its prokaryotic community is comprehensively investigated. Sponge specimens displayed lower microbial diversity compared with surrounding seawater. At the phylum level, prokaryotic communities were consistently dominated by Proteobacteria, followed by Cyanobacteria, Chloroflexi, Acidobacteria, Actinobacteria, Gemmatimonadetes, Thaumarchaeota and Poribacteria. Operational taxonomic unit (OTU) analysis alternatively showed that the most abundant symbiont was the sponge-specific cyanobacterial species “Candidatus Synechococcus spongiarum”, followed by OTUs belonging to the unidentified Chloroflexi and Acidobacteria. Phylogenetic tree based on 16S-23S internal transcribed spacer regions indicated that the dominated cyanobacterial OTU represented a new clade of “Ca. Synechococcus spongiarum”. More reliable metagenomic data further revealed that poribacterial symbionts were highly abundant and only secondary to the cyanobacterial symbiont. One draft genome for each of the Cyanobacteria, Chloroflexi and Acidobacteria and three poribacterial genomes were extracted from the metagenomes. Among them, genomes affiliated with the Chloroflexi and Acidobacteria were reported for the first time in sponge symbionts. Eukaryotic-like domains were found in all the binned genomes, indicating their potential symbiotic roles with the sponge host. The high quality of the six recovered genomes of sponge symbionts from the sponge D. elegans makes it possible to understand their symbiotic roles and interactions with the sponge host as well as among one another .